Encyclopedia of social measurement - Kempf Leonard, Kimberly (Gale virtual reference library., 2005)
"Captures the data, techniques, theories, designs, applications, histories, and implications of assigning numerical values to social phenomena. Covers all core social science disciplines and presents a comprehensive summary of observational frameworks and mathematical models. Also offers tools, background information, qualitative methods, and guidelines for structuring the research process"--About this publication webpage.